TOTAL CHOLESTEROL LEVELS AND DEGREES OF HYPERTENSION IN THE ELDERLY HYPERTENSION - Popi Sopiah; Popon Haryeti; Nunung Siti Sukaesih; Reni Nuryani; Sri Wulan Lindasari (Universitas Padjadjaran, 2021)
Hypertension is still the leading cause of death in the elderly. Physiological and degenerative processes in the elderly also cause changes in cholesterol levels. It is known that hypercholesterolemia is a risk factor for hypertension. If hypertension and hypercholesterolemia occur in the elderly, it is hazardous for the health of the elderly. Total cholesterol is an important parameter to assess the risk of hypertension. The study aimed to obtain an overview of the total cholesterol profile and the degree of hypertension in elderly hypertension. The research design was a cross-sectional method. Nonprobability sampling with accidental sampling was chosen as a sample selection technique. The sample size was 103. The quantitative descriptive data analysis was presented in a frequency distribution. The results of the study provide an overview of the distribution of elderly hypertension, referring to ACC/AHA classification at hypertension grade I (39.8%), hypertension grade II (35%), and hypertension grade III (25.2%). Meanwhile, the total cholesterol profile was in the desirable range (44.7%), borderline high (26.2%), and high (29.1%). The conclusion that the highest cholesterol levels are in the normal range with the highest degree of hypertension in category I. Future research should examine the factors that cause hypertension in the elderly with normal cholesterol levels.